The inverted pendulum in control theory and robotics : from theory to new innovations - Boubaker, Olfa; Iriarte, Rafael (The Institution of Engineering and Technology, 2017)
This book provides an overall picture of historical and current trends and developments in nonlinear control theory, based on the simple structure and rich nonlinear model of the inverted pendulum.
Keywords: Estimation theory.; Linear systems.; Nonlinear control theory.; elektronické knihy; electronic books